PRONOMINAL VARIATION OF THE SECOND PERSON SINGULAR IN PERSONAL LETTERS IN BRAZILIAN PORTUGUESE: AN INTEGRATIVE LITERATURE REVIEW (PERcursos Linguísticos, 2026)
This article presents an integrative literature review on the use of second-person singular subject pronouns in personal letters written in Brazilian Portuguese, with a diachronic approach. The analysis of 14 empirical studies, covering letters dated between 1850 and 1999, reveals a gradual replacement of the pronoun tu by você, with significant variation depending on the letter genre, region, level of intimacy between interlocutors, and syntactic context. The results highlight the coexistence of treatment subsystems marked by different patterns of agreement and pronominal reference. The data show that the form vossa mercê, predominant in the 19th century, gave way to você, which assumed more neutral and informal functions in the 20th century. The study concludes that the variation between tu and você reflects ongoing linguistic changes conditioned by social and discursive factors, and that personal letters are privileged documents for analyzing such variation.
Keywords: Personal pronouns; Tu and Você; Personal letters; Language variation; Historical sociolinguistics